The pedagogical affordances of e-portfolio in learning how to teach: A systematic review - Raja Nor Safinas Raja Harun; Mohd Hafiz Hanif; Goh Swee Choo (Studies in English Language and Education, 2021)
The advances in technology have paved the way for student centred learning environment which allows for higher students’ engagement, active participation, deep meaningful learning, and critical thinking. One of the technology applications which have gained popularity at the beginning of the 1990s is the use of e-portfolio. Studies in many professional fields have shown exceptional findings on the adoption of e-portfolio. Nonetheless, the development of e-portfolio affordances over a period of time has yet to be explored to ascertain its usefulness particularly in the area of teacher education. This article presents the process of systematic literature on the e-portfolio pedagogical affordances in teacher education programs and issues to be addressed for successful implementation. Using the content analysis method, 28 articles which focused on e-portfolio, teacher education, English as a second language, scientific research, and secondary school were reviewed. The findings of the review have mainly shed positive lights on its use in documenting student teachers’ learning experiences particularly on assisting and assessing student teachers learning how to teach. This article implicates the relevance of having a holistic view and understanding of the e-portfolio pedagogical affordances and the need to recognize issues to be addressed prior to its implementation in a teacher education program. With this understanding, the university and teacher education institutions can have a well-defined policy on the adoption of e-portfolio into their teacher education programs.